Orbits of comets C/1848 P1 (Petersen) and C/1848 U1 (Petersen) - Branham, Richard Lacy (2014)
Comets C/1848 P1 (Petersen) and C/1848 U1 (Petersen) are ones of a large number of comets with parabolic orbits. Given that there are sufficient observations, 67 in right ascencion and 61 in declination for the former and 144 in right ascension and 144 in declination for the latter, it proves to be possible to calculate better orbits. The C/1848 P1's orbit is hyperbolic, although statistically indistinguishable from a parabola. This object, therefore, cannot be considered as an NEO. C/1848 U1's orbit is also hyperbolic, but with no indication of a possible extrasolar origin.